Luminescent electrochromic devices for smart windows of energy-efficient buildings - Fernandes, Mariana (2018)
This research was funded by National Funds through the Foundation for Science and Technology (FCT) and by FEDER funds through the POCI-COMPETE 2020, Operational Programme Competitiveness and Internationalisation in Axis I: Strengthening research, technological development and innovation (FCT Ref. UID/QUI/00616/2013, POCI-01-0145-FEDER-007491, FCT Ref. UID/Multi/00709/2013), and LUMECD (POCI-01-0145-FEDER-016884 and PTDC/CTM-NAN/0956/2014).